LOCATION-BASED ADVERTISING: INTRUSIVENESS AND IRRITATION - Senny Handayani Suarsa (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2020)
Location-based Advertising (LBA) is a marketing strategy using cellular devices such as smartphones to offer products to potential customers at the nearest sales or service location. Intrusiveness and irritation are disorders that appear in the LBA. The conceptual framework of the research is built on the Advertising Avoidance Theory. Data collection was carried out with a self-administered survey involving 356 Politeknik Pos Indonesia students. The results showed that Intrusiveness and Irritation had a positive and significant effect on consumer attitudes toward LBA messages. Meanwhile, Intrusiveness has a negative and significant impact on consumer purchase intention, while irritation has a positive and significant impact on purchase intention. The more positive consumer attitudes towards LBA, the more positive the consumer's intention to buy.